Classical Myths and American Abstract Expressionism: The Case of William Baziotes - Aguirre, Mercedes (Collectanea Philologica, 2016)
Abstract Expressionism can be seen as a valid expression of the crisis of ‘Modern Man’ and, as a result, it assumed a central role in the cultural debate of its time. Within this crisis can be situated a new form of representing the ancient myths. William Baziotes, an artist who belongs to the New York School, becomes a modern ‘myth-maker’ who creates metaphors and symbols which refer to primitive cultures and primeval worlds. If a few of his paintings allude in their title to a particular Classical myth, others, without a specific title referring to a myth, have strong affinities with mythology. Classical myths seem to be entwined with the artist’s own personal myths, interpreted through his own language and his own symbols.